Acute Exacerbation of Chronic Obstructive Pulmonary Disease: Influence of Social Factors in Determining Length of Hospital Stay and Readmission Rates - Alyson WM Wong; Wen Q Gan; Jane Burns; Don D Sin; Stephan F van Eeden (Canadian Respiratory Journal)
BACKGROUND: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is the leading reason for hospitalization in Canada and a significant financial burden on hospital resources. Identifying factors that influence the time a patient spends in the hospital and readmission rates will allow for better use of scarce hospital resources.